Swingin´ his hands faster than Karate Kid : Der gehörlose Rapper Signmark und Gebärdensprachen im HipHop - Thoma, Nadja; Lehto, Annamaria; Justus Liebig University Giessen (My University, 2011)
In 2006, the deaf rapper Signmark captured the charts of his home country Finland with an album that consists of a CD and a DVD with the first raps in Sign Language worldwide.The aim of the album is to gain visibility to the history and society of deaf people and to position Sign Languages as legitimate languages on stage.On the one hand, the hip-hop culture is often described as a culture of marginalized groups. Rap lyrics are a site where languages and identities are refashionedand where speakers of marginalized communities and languages increase visibility of their languages and call language ideologies, politics and hierarchies into question.On the other hand, (spoken) language and voice are seen as constitutive elements of rap.This article addresses the relationship between the call for authenticity in rap which is strictly bound to the materiality of voice, and the use of Sign Lanugage, which can be interpreted as the authentic use of the cultural and linguistic traditions of deaf people.
Keywords: ddc:780